2000
DOI: 10.1038/71732
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in a new photoreceptor-pineal gene on 17p cause Leber congenital amaurosis

Abstract: Leber congenital amaurosis (LCA, MIM 204000) accounts for at least 5% of all inherited retinal disease and is the most severe inherited retinopathy with the earliest age of onset. Individuals affected with LCA are diagnosed at birth or in the first few months of life with severely impaired vision or blindness, nystagmus and an abnormal or flat electroretinogram (ERG). Mutations in GUCY2D (ref. 3), RPE65 (ref. 4) and CRX (ref. 5) are known to cause LCA, but one study identified disease-causing GUCY2D mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
202
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(206 citation statements)
references
References 10 publications
1
202
1
2
Order By: Relevance
“…The following genes are known to be associated with LCA: GUCY2D, RPE65, SPATA7, AIPL1, LCA5, RPGRIP1, CRX, CRB1, CEP290, IMPDH1, RD3, RDH12, KCNJ13, LRAT and TULP1. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] It is difficult to estimate the proportion of patients with mutations in the different genes, as some, such as IMPDH1 (LCA11) is considered to be rare, other, as CEP290 accounts for almost 20%, and for some such as TULP1 and LRAT the number is uncertain. One of the most studied LCA genes is CRB1 at 1q31q32.1, which consists of 12 exons and encodes a protein Crumbs homologue that participates in determination and maintenance of photoreceptor architecture.…”
Section: Introductionmentioning
confidence: 99%
“…The following genes are known to be associated with LCA: GUCY2D, RPE65, SPATA7, AIPL1, LCA5, RPGRIP1, CRX, CRB1, CEP290, IMPDH1, RD3, RDH12, KCNJ13, LRAT and TULP1. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] It is difficult to estimate the proportion of patients with mutations in the different genes, as some, such as IMPDH1 (LCA11) is considered to be rare, other, as CEP290 accounts for almost 20%, and for some such as TULP1 and LRAT the number is uncertain. One of the most studied LCA genes is CRB1 at 1q31q32.1, which consists of 12 exons and encodes a protein Crumbs homologue that participates in determination and maintenance of photoreceptor architecture.…”
Section: Introductionmentioning
confidence: 99%
“…60%) [Perrault et al, 1999;Hanein et al, 2004]. Up to date, 13 LCA genes have been mapped, 10 of which have been identified: GUCY2D/retGC1 [Perrault et al, 1996], RPE65 [Marlhens et al, 1997], CRX [Swaroop et al, 1999], AIPL1 [Sohocki et al, 2000], RPGRIP1 [Dryja et al, 2001;Gerber et al, 2001], CRB1 [den Hollander et al, 2001;Gerber et al, 2002], LRAT [Thompson and Gal, 2003], TULP1 , RDH12 [Janecke et al, 2004;Perrault et al, 2004], CEP290 [den Hollander et al, 2006;Perrault et al, 2007]. Mutations in 3/10of them were shown to account for LCA type I (GUCY2D, RPGRIP1, CEP290) while, although less frequent, LCA type II was hitherto accounted for by mutations in 7/10 genes (RPE65, CRX, AIPL1, CRB1, LRAT TULP12, RDH12) [Perrault et al, 1999;Hanein et al, 2004;Perrault et al, 2004;Perrault et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…82,83 A number of loci and mutated genes have been implicated in LCA. 83,84 One of these genes, AIPL1 (aryl-hydrocarbon receptor-interacting protein-like 1), is involved in LCA4.…”
Section: Peptidyl-prolyl Cis-trans Isomerase (Ppiase) Leber Congenitamentioning
confidence: 99%
“…82,86,87 Comparative analyses of primary structures revealed that all mammalian AIPs are conserved and are related to the FKBP group of chaperones. 85 The FKBP chaperones function in steroid receptor signaling, heat-shock response, and immunosuppression.…”
Section: Peptidyl-prolyl Cis-trans Isomerase (Ppiase) Leber Congenitamentioning
confidence: 99%